Knowledge-embedded deep reinforcement learning for real-time dispatch of wind-solar-hydro hybrid generation systems - Yuanyu Ge; Jun Xie; Shuo Feng; Jiaqi Chang; Denghui Fu (Journal of Cleaner Production, 2026)

Study of the gut microbial diversity of Mytilus coruscus with different growth rates - Jiaxin Gao; Xiaoao Yang; Pengzhi Qi; Liangming Chen; Peipei Fu; Denghui Zhu (Folia Microbiologica, 2025)

Interfacial chemical bonds enhanced photocatalytic performance of kaolinite/NiFe layered double oxide heterostructure for photocatalytic activated peroxymonosulfate - Cheng Li; Huihua Jing; Bing Lv; Donghang Zhou; Shuguang Fu; Xiong Tang; Zhengpei Wang; Weiguang Wu; Denghui Jiang (Applied Clay Science, 2024)

Estimation of PM2.5 Mass Concentration from Visibility - Denghui Ji; Zhaoze Deng; Xiaoyu Sun; Liang Ran; Xiangao Xia; Disong Fu; Zijue Song; Pucai Wang; Yunfei Wu; Ping Tian; Mengyu Huang (Advances in Atmospheric Sciences, 2020)
Aerosols in the atmosphere not only degrade visibility, but are also detrimental to human health and transportation. In order to develop a method to estimate PM 2.5 mass concentration from the widely measured visibility, a field campaign was conducted in Southwest China in January 2019. Visibility, ambient relative humidity (RH), PM 2.5 mass concentrations and scattering coefficients of dry particles were measured. During the campaign, two pollution episodes, i.e., from 4–9 January and from 10–16 January, were encountered. Each of the two episodes could be divided into two periods. High aerosol hygroscopicity was found during the first period, when RH was higher than 80% at most of the time, and sometimes even approached 100%. The second period experienced a relatively dry but more polluted condition and aerosol hygroscopicity was lower than that during the first period. An empirical relationship between PM 2.5 mass concentration and visibility (ambient aerosol extinction) under different RH conditions could thus be established. Based on the empirical relationship, PM 2.5 mass concentration could be well estimated from visibility and RH. This method will be useful for remote sensing of PM 2.5 mass concentration.